The memo ebook A novel. - Dodes, Rachel (2024)
"The perfect summer read: a novel both quick and funny." — Airmail "A total joyride of a novel. The Memo is a funny, fascinating exploration of love, friendship, ambition and what it truly means to live a good life. I loved it."—J. Courtney Sullivan, New York Times bestselling author of Commencement, Maine, and Friends and Strangers If you could rewrite your life story, would you dare? That's the question at the heart of this funny, sharp and propulsive debut novel about love, life, and a woman finding herself and what it means to be happy and successful. Do you ever feel like your life doesn't measure up to everyone else's—and wonder if you just didn't get the memo helping you make the right choices? Jenny Green dreads her upcoming college reunion. Once top of her class, the thirty-five-year-old finds herself stuck in a life that isn't the one she expected. Her promising career has flamed out (literally) and her deadbeat boyfriend is cheating on her (again). All her friends seem to have it all figured it out, enjoying glittering lives and careers that she can only envy from the sidelines. Did she just not get the memo they all did? As it turns out, she didn't! When she arrives at her alma mater for the festivities, she receives a text from an unlisted number. "Jenny Green: please collect your memo." Somewhere on campus, a discreet female-led organization provides comprehensive memos to select students, a set of instructions that are a blueprint for success. The first time around, Jenny didn't receive hers. Now, she's being given the second chance she wants—an opportunity to relive her life and make all the right decisions this time around. But at what price? Smart, addictive, bittersweet, and ultimately triumphant, The Memo will enchant readers of In Five Years and Cassandra in Reverse as well as fans of Emma Straub and Maria Semple.